Indonesia's Compliance with ACIA and its Implications for MSME Development - Rivaldi, M.Rivaldi Husaini Hardiansyah; Djunaidi, Djunaidi; Rivardi, Ferdiansyah (CV. DYOQU PUBLISHING MANAGEMENT, 2025)
Background: Indonesia's engagement with the ASEAN Comprehensive Investment Agreement (ACIA) is intended to promote regional investment flows and support domestic economic development, especially for Micro, Small, and Medium Enterprises (MSMEs). Despite formal compliance, structural and institutional barriers remain, limiting the benefits MSMEs receive. Aims: This study aims to evaluate the extent of Indonesia’s compliance with ACIA through three stages (output, outcome, and impact) and to analyse its influence on MSME development in Indonesia. Methods: A descriptive qualitative approach was adopted, grounded in Ronald B. Mitchell’s compliance theory. Data were obtained from policy documents, academic literature, and official reports. Thematic content analysis was used to assess how formal commitments translate into domestic policy adjustments and real economic impacts for MSMEs. Result: Indonesia has shown formal compliance by ratifying ACIA via Presidential Regulation No. 49/2011. Policy adjustments include initiatives promoting partnerships between foreign investors and local MSMEs. However, the impact remains limited due to poor digital literacy, weak institutional support, and a lack of targeted incentives. Although access to capital and markets has marginally improved, substantial transformation has yet to occur. Conclusion: While Indonesia has formally complied with ACIA and introduced policies to empower MSMEs, the effectiveness of these measures is hindered by systemic weaknesses. The compliance process reflects symbolic and procedural alignment but lacks substantive integration at the grassroots economic level. Future efforts must focus on building institutional capacity, improving MSME readiness, and designing inclusive financing schemes. This study contributes to international regime theory by bridging global policy frameworks with domestic development agendas, positioning MSMEs as critical agents in the global political economy.